The Role of Sustainable Human Resource Management and Organizational Excellence in Saudi Arabia: Evidence from King Khalid University - Mostafa, Engy Ahmed Abdel Ghany; Alhaj, Abeer Bakri Siralkhatim; Mohammad, Reda Abdelfattah; Hammami, Mariam Hussein Hadi; Musa, Arafa Gebreil; Fadul, Mohammed Mustafa M. Y.; Osman, Anjom Ahmed; Alahmari, Abdullah Moshabbab Omran (Migration Letters, 2024)
The aim of this study is to investigate the effect of Sustainable Human Resource Management (HRM) in Organizational Excellence (OE) among universities’ academic and administrative staff in Saudi Arabia. Due to the lack of studies of sustainable HRM in universities, this study selected the King Khalid University (KKU) as a case study. Moreover, the quantitative approach is being applied to lead the methods of this study. So, the data collect based on online self-administrated questionnaire. Then, the data was analysis using the Structural Equation modeling (ESM) technique (Smart-PLS 4.0) and SPSS 20.0 as well. The results indicated that there is a positive relationship between sustainable HRM and OE in Saudi Arabian universities. that means, when the policymakers investing more in sustainable HRM, they would be getting advance level of excellency in their universities and overall of employees’ performance. Ultimately, the implications and future trajectories were discussed.